Defining subspecies, invalid taxonomic tools, and the fate of the woodland caribou - Geist, Valerius (Rangifer, 2007)
If my argument is valid, then true woodland caribou are only the very few, dark, smallmanned caribou scattered across the south of caribou distribution. They need the most urgent of attention.